Technological Literacy and Epistemic Cognition: Relationships Affecting Student Learning Outcomes in Higher Education - Permata, Santy Dinar; Putra, Arda Purnama; Aishnabila, Shinta; Hasanah, Maulidathul; Fitri, Auliya (Proceedings Series of Educational Studies, 2024)
The real challenge faced by students today is the low level of technological literacy in Indonesia. At the same time, the rapid flow of technological developments continues to occur and demands to have workforce competencies that are able to think critically, solve problems and provide solutions appropriately. This study aims to determine the correlation of technological literacy and epistemic cognition of elementary and preschool education, state university of Malang students. The type of research used is quantitative with the number of samples used as many as 120 students. Data were collected using tests and project assessments. Furthermore, the data were analyzed using the Spearman correlation test in a non-parametric method to measure the strength and direction of the relationship between two variables. The results showed that the correlation data was 0.860. The data explains that there is a relationship between technological literacy and epistemic cognition. Based on these data, it can be concluded that a significant correlation is observed in technological literacy and student epistemic cognition. Increasing technological literacy is the basis for improving the achievement of student learning outcomes. not only increases in numbers but also relates to the ability to think critically, solve problems and find solutions effectively.